Memaksimalkan Pertanian Berkelanjutan Dengan Menghitung Kebutuhan Air Irigasi Dengan Akurat - Friski Dermawan Zebua; Hamedoni Harita (CV. SINAR HOWUHOWU, 2026)
Sustainable agriculture requires efficient resource management to ensure optimal crop production without harming the environment. Water is a critical factor in agricultural processes, making accurate calculation of irrigation water requirements essential for efficient water use. This study develops a technology-based method, incorporating the Penman-Monteith model, remote sensing technology, geographic information systems (GIS), and artificial intelligence (AI), to accurately calculate irrigation water needs. The method also integrates real-time data from soil moisture sensors to enhance calculation accuracy. The findings indicate that this approach optimizes water use, supports agricultural productivity, and conserves water resources. This approach is expected to enable sustainable agriculture across diverse local conditions.